2015
DOI: 10.3390/rs70302283
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Shrubland Drying in the South-East Mediterranean, 1995–2010: Water-Use-Efficiency-Based Mapping of Biomass Change

Abstract: Recent climate studies of the South-Eastern Mediterranean indicate an increase in drought frequencies and decreasing water resources since the turn of the century. A four-phase methodology was developed for assessing above-ground biomass changes in shrublands caused by these recent trends. Firstly, we generalized the function SB = 0.008MAP 1.54 describing the shrublands above-ground biomass (SB) dependence on mean annual precipitation (MAP) for areas of full shrub cover. Secondly, relationships between MAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(46 reference statements)
2
9
0
Order By: Relevance
“…A statistically significant negative trend in FPAR values in all seasons (although quite weak in DJF) was identified in the transition zone between the northern Negev desert and the Mediterranean climate region. This finding corresponds to other studies that found a statistically significant decrease in vegetation cover and in productivity along this desert fringe area, using MODIS derived time series of FPAR (Levin, 2016), Landsat images which enabled to identify the drying of shrubland (Shoshany and Karnibad, 2015) and the drying of planted forests (Dorman et al, 2013). Such increased dry conditions may well enhance the probability of wildfires to propagate, as has been found in previous studies (Kutiel, 2012 …”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…A statistically significant negative trend in FPAR values in all seasons (although quite weak in DJF) was identified in the transition zone between the northern Negev desert and the Mediterranean climate region. This finding corresponds to other studies that found a statistically significant decrease in vegetation cover and in productivity along this desert fringe area, using MODIS derived time series of FPAR (Levin, 2016), Landsat images which enabled to identify the drying of shrubland (Shoshany and Karnibad, 2015) and the drying of planted forests (Dorman et al, 2013). Such increased dry conditions may well enhance the probability of wildfires to propagate, as has been found in previous studies (Kutiel, 2012 …”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…The NDVI has found extensive use in various applications such as space-time trend analysis of vegetation health (Shoshany and Karnibad [8]), mapping of invasive species (Paz-Kagan et al [5]), and identification of environmental factors that influence vegetation (Karnieli et al [9]). Despite widspread adoption, several notable limitations of this index have been documented.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…However, observations show large difference in the values of NDVI obtained for similar values of vegetation cover, when comparing across regions with different levels of precipitation [11]. Such differences can result in under-detection of forests, especially in regions with low precipitation load.…”
Section: Introductionmentioning
confidence: 97%
“…LAI derived from remotely sensed data is usually based on parametrization of the Fractional Vegetation Cover (FVC). Therefore, from the remote-sensing perspective it is difficult to distinguish between the two causes of change, although in many cases increasing inputs of precipitation will be associated with an increase in both vegetation cover, plant biomass, and LAI [11,17].…”
Section: Introductionmentioning
confidence: 99%